High Burden of Active Syphilis and Human Immunodeficiency Virus/Syphilis Coinfection Among Men Who Have Sex With Men, Transwomen, and Genderqueer Individuals in Zimbabwe. Issue 2 (10th February 2022) - Parmley, Lauren E.; Chingombe, Innocent; Wu, Yingfeng; Mapingure, Munyaradzi; Mugurungi, Owen; Samba, Chesterfield; Rogers, John H.; Hakim, Avi J.; Gozhora, Perpetua; Miller, Sophia S.; Musuka, Godfrey; Harris, Tiffany G.
Abstract : A respondent-driven sampling survey among men who have sex with men and transwomen, and genderqueer in Zimbabwe found that active syphilis overall and among participants living with HIV was >6 times and 4 times higher, respectively, than estimates among the general adult male population in the country. Abstract : Background: Syphilis increases human immunodeficiency virus (HIV) acquisition risk and impacts the immunologic and virologic response among people living with HIV (PLHIV). We assessed the prevalence of active or current syphilis and HIV/syphilis and their correlates among men who have sex with men (MSM), transwomen, and genderqueer (TGW/GQ) individuals in Zimbabwe. Methods: Among a respondent-driven sample of MSM and TGW/GQ who were tested for HIV and syphilis in Harare and Bulawayo, Zimbabwe in 2019 (n = 1511), multiple logistic regression was used to assess correlates of active syphilis. Unadjusted logistic regression was used among PLHIV (n = 340) due to small sample size. All analyses were unweighted as data did not reach convergence for HIV. Results: Prevalence of active syphilis overall and among PLHIV was 5.5% and 10.1%, respectively, in Harare, and 5.6% and 11.0%, respectively, in Bulawayo. Participants were more likely to have active syphilis if they were PLHIV (adjusted odds ratio [aOR], 2.2; 95% confidence interval [CI], 1.4–3.6), aged 25–34 years (aOR, 2.2 years; 95% CI, 1.3–3.8 years; reference, 18–24 years), or self-report sexually transmitted infection symptoms (aOR, 1.8; 95% CI, 1.1–3.0). Compared with Bulawayo TGW/GQ, MSM in Harare (aOR, 0.2; 95% CI, 0.1–0.5) and Bulawayo (aOR, 0.2; 95% CI, 0.1–0.4), and TGW/GQ in Harare (aOR, 0.2; 95% CI, 0.1–0.6) were less likely to have active syphilis. Among PLHIV, coinfection was 13.0% among TGW/GQ and 9.7% among MSM. Odds of coinfection were higher for those aged 25 to 34 years (OR, 3.7 years; 95% CI, 1.2–11.1 years) and lower among Harare MSM (OR, 0.2; 95% CI, 0.1–0.7), Bulawayo MSM (OR, 0.1; 95% CI, 0.0–0.4), and Harare TGW/GQ (OR, 0.1; 95% CI, 0.0–0.4) compared with Bulawayo TGW/GQ. Conclusions: Findings highlight a high burden of syphilis among MSM and TGW/GQ and underscore the importance of HIV/syphilis detection and improved service delivery for these groups.